Improved COVID-19 Outcomes following Statin Therapy: An Updated Systematic Review and Meta-analysis. (24th September 2021) - Vahedian-Azimi, Amir; Mohammadi, Seyede Momeneh; Banach, Maciej; Beni, Farshad Heidari; Guest, Paul C.; Al-Rasadi, Khalid; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract : Background . Although vaccine rollout for COVID-19 has been effective in some countries, there is still an urgent need to reduce disease transmission and severity. We recently carried out a meta-analysis and found that pre- and in-hospital use of statins may improve COVID-19 mortality outcomes. Here, we provide an updated meta-analysis in an attempt to validate these results and increase the statistical power of these potentially important findings. Methods . The meta-analysis investigated the effect of observational and randomized clinical studies on intensive care unit (ICU) admission, tracheal intubation, and death outcomes in COVID-19 cases involving statin treatment, by searching the scientific literature up to April 23, 2021. Statistical analysis and random effect modeling were performed to assess the combined effects of the updated and previous findings on the outcome measures. Findings . The updated literature search led to the identification of 23 additional studies on statin use in COVID-19 patients. Analysis of the combined studies (n = 47 ; 3, 238, 508 subjects) showed no significant effect of statin treatment on ICU admission and all-cause mortality but a significant reduction in tracheal intubation (OR = 0.73, 95% CI: 0.54-0.99, p = 0.04, n = 10 studies). The further analysis showed that death outcomes were significantly reduced in the patients who received statins during hospitalization (OR = 0.54, 95% CI: 0.50-0.58, p < 0.001, n = 7 studies), with no such effect of statin therapy before hospital admission (OR = 1.06, 95% CI = 0.82 -1.37, p = 0.670, n = 29 studies). Conclusion . Taken together, this updated meta-analysis extends and confirms the findings of our previous study, suggesting that in-hospital statin use leads to significant reduction of all-cause mortality in COVID-19 cases. Considering these results, statin therapy during hospitalization, while indicated, should be recommended.